Efficiency of glued finger joint / Norizah Omar - Omar, Norizah (1995)
The project covers the Finite Element analysis of the glued wood joint under tensile loads with different tip thickness and lap length. The analysis of the wood joints covers the mini finger joint. The results' from the experimental (Selbo) analysis i.e tensile strength and efficiency were used as a comparison with the data from the computer analysis The objectives were to obtain the stresses and displacement of the joint using the ANSYS program package. Isoparametric solid 2D element i.e PLANE 42 are used in analysis. Linear finite element model and the aspect ratio limited to 1:10, were used in order to reduce the errors. It was found that the value of efficiency of the finger joint increased with the decreasing tip thickness (t), slope (s) and increasing of the glue line length.